2017
DOI: 10.1039/c7cp02324c
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of ammonium bisulfate formation and decomposition over V/WTi catalysts for NH3-selective catalytic reduction at various temperatures

Abstract: In this study, the mechanism of ammonium bisulfate (ABS) formation and decomposition over V/WTi for the NH-selective catalytic reduction (SCR) at various temperatures was deeply investigated. Bridged bidentate, chelating bidentate, and tridentate sulfates bound to TiO were formed as dominant intermediates at 200, 250, and 300 °C, respectively. These sulfates reacted with affinitive ammonium species to form ammonium (bi)sulfate species and also covered the active sites and embedded the VOSO intermediates, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 35 publications
1
44
0
Order By: Relevance
“…Judging from its TPD trace it was confirmed that the virgin monolith contained some sulfur (see Table 1), likely in the form of sulfate species deliberately added during catalyst preparation in order to promote the SCR activity by increasing the number of acid sites for NH3 adsorption [17]. By comparison with the TPD results of reference sulfate compounds, the SO2 peaks between 400 and 600 °C were associated with the decomposition of sulfate species bonded to titania and of VOSO4 species [20,23], while the decomposition of iron sulfates might contribute at higher temperatures [24]. The NH 3 TPD of the aged sample carried out without pre-adsorbing ammonia at 100 • C (Figure 4), shows a more intense signal starting at about 210 • C, with a peak at 315 • C, and ending at the same temperature observed for the fresh catalyst.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Judging from its TPD trace it was confirmed that the virgin monolith contained some sulfur (see Table 1), likely in the form of sulfate species deliberately added during catalyst preparation in order to promote the SCR activity by increasing the number of acid sites for NH3 adsorption [17]. By comparison with the TPD results of reference sulfate compounds, the SO2 peaks between 400 and 600 °C were associated with the decomposition of sulfate species bonded to titania and of VOSO4 species [20,23], while the decomposition of iron sulfates might contribute at higher temperatures [24]. The NH 3 TPD of the aged sample carried out without pre-adsorbing ammonia at 100 • C (Figure 4), shows a more intense signal starting at about 210 • C, with a peak at 315 • C, and ending at the same temperature observed for the fresh catalyst.…”
Section: Resultsmentioning
confidence: 91%
“…Therefore, from the onset temperature of desorption, it can be argued that the last temperature the catalyst experienced in the SCR reactor was around 210 • C. The total amount of desorbed ammonia was lower (0.075 mmol/g) than the amount desorbed from the fresh sample due to the lack of NH 3 pre-adsorption step at 100 • C. Nevertheless, in the high-temperature range (above 300 • C), the NH 3 desorption peak for the aged catalyst exceeded that of the fresh catalyst. This result strongly suggests the decomposition of ammonium salts, like sulfate and bisulfate, probably formed by the reaction between NH 3 and SO 2 /SO 3 or other superficial sulfates which were eventually deposited on the catalyst surface due to the low temperature of operation [7,11,18,[20][21][22]. Notably, the content of gaseous SO 2 in the exhaust gas after the desulfurization unit is quite low (in the single digit ppmv range) [15].…”
Section: Resultsmentioning
confidence: 99%
“…The high-temperature gas (>450 C) from the hot-blast stove was used to heat and vaporise aqua ammonia, or in situ regenerate the honeycomb catalyst in the SCR reactors through the decomposition of the ammonium sulfate species above 450 C. 13,14 Compressed air was supplied for the ammonia evaporator to dilute the vaporized NH 3 and for the soot blower to clean the ash deposited on the catalytic surface. Four SCR reactors were designed for use alternately on a line.…”
Section: Technological Process Of the Project Casementioning
confidence: 99%
“…The addition of WO 3 is helpful to increase the Brønsted acid sites, enhance the reaction activity by improving the redox capacity at low temperatures, and to restrain the phase transition, but it still faces erosion of hydrogen sulfate. Li, C. et al [48] studied the formation and decomposition of ammonium bisulfate over V 2 O 5 -WO 3 /TiO 2 catalysts at different temperatures. With the combination of ammonium hydrogen sulfate (ABS) and metal oxides (WO 3 and TiO 2 ), electrons deviate from the sulfate, thereby weakening the stability of the ABS and reducing the decomposition temperature.…”
Section: Performance Improvement Of Vanadium Based Catalystsmentioning
confidence: 99%